Conflicts Due To Women Leadership Roles In Hospitality Sector - Purohit, Priyanka (International Journal of Psychosocial Rehabilitation, 2019)
Analysts have asserted that businesses with a higher proportion of female executives enjoy higher profit margins and better key performance indicators. Furthermore, a research of roughly 22,000 publicly listed businesses in 91 countries found that the presence of women on the top leadership team was positively correlated with higher profits. Sales, ROI, and net profit, as well as customer and employee happiness, are just some of the KPIs that have been shown to grow with a more diverse staff. At least a 6% increase in net profit margins was found when the Peterson Institute for International Economics & EY evaluated the financial data of 21,980 publicly listed firms throughout the world in 91 different industries and sectors. The number of firms led by women on the 2016 Fortune 500 list fell to 21 from 24 the year before. The hospitality sector might do more to encourage and enable women to enter and advance in the field of their choice.